Deli River Tourism Educational Model by Avros Park in Developing Economic Potential - Uswah Hasanah; Mutiah Khaira Sihotang (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
A tourist attraction that can be developed to support the community’s economy is natural resources. One of the natural resources is a river. The river as a source of water is very important in meeting the needs of society and enhancing national development. This is also intended as an implementation of the provisions of Law Number 11 of 1974 concerning irrigation, namely that in the context of utilizing and preserving rivers, it is deemed necessary to make arrangements regarding rivers which include protection, development, use, and control of rivers with government regulations. Deli River is one of the rivers in the city of Medan, which, if you look at history during the Deli kingdom, was the vein of trade. However, it is very unfortunate that at this time the existence of the Deli River was starting to be polluted by the large amount of river pollution carried out by the community. The efforts to preserve the river are carried out by Avros Park Medan, through its tourism vehicles trying to provide education to the public working with foundations concerned with the river environment. The purpose of this research is to conduct an assessment of the tourist education model that can be developed by Avros Park in an effort to preserve the environment of the Deli River and in an effort to attract tourists to visit Avros Park. The type of research is descriptive with a qualitative approach. Data collection was carried out through observation, interviews, and documentation studies. The design of the educational tourism model in this research consists of a tutorial and exploratory educational method.